Implementasi Robot Mobile Dual Mode Berbasis Arduino Uno sebagai Media Pembelajaran Ekstrakulikuler Robotik - Nazil Fikri Hidayatullah; Abdul Halim; Rudianto Rudianto; Mochammad Darip (Bulletin of Information Technology (BIT), 2026)
The advancement of robotics technology offers significant opportunities to enhance practice-based learning in vocational education. However, the implementation of robotics learning at the vocational high school (SMK) level still faces limitations in interactive learning media and low student engagement. This study aims to develop and evaluate a dual-mode mobile robot based on Arduino Uno as a learning medium for robotics extracurricular activities at SMK Negeri 11 Kabupaten Tangerang. The research method employs a Research and Development (R&D) approach with a prototyping model, including problem identification, system design, implementation, testing, and evaluation stages. The developed system integrates two operational modes: an automatic mode (obstacle avoider) and a manual control mode using Bluetooth communication. The results indicate that the system operates stably and responsively, with an average response time of less than one second and acceptable sensor accuracy. Learning evaluation through questionnaires shows an improvement in student interest and understanding, with scores above 78%. This study contributes to the development of interactive and practical robotics-based learning media, which enhances student engagement in the learning process.